DEVELOPING WEB-BASED TEACHING MATERIALS ON THE SUBJECT OF SCHOOL CURRICULUM DEVELOPMENT - Ade Vidianti; Johan Eka Wijaya DN (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The development of science and technology has changed the elements in all fields, especially education. The learning patterns have also changed; one of which is using computer-based or internet / web-based learning, such as: E-learning, online courses, web-based education, and others. This paradigm shift sometimes requires lecturers to be more creative in delivering learning materials to students, especially, in this research, in the subject of school curriculum development. This aims to increase the effectiveness and flexibility of learning. In its implementation, the school curriculum development subject still ituilize printed teaching materials during the learning process. The purpose of this research was to develop webbased teaching materials for the subject of school curriculum development. This research applied research and development method with ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The development of web-based teaching materials in this research was assessed through the expert review stage with an accumulation of assessment results from media experts, design experts, linguists, and media experts. The result showed that the percentage of the expert review was 86% very good category. Then, the percentage of the individual test (one to one) was 85% with very good category. After that, the percentage of small group test was 85% with very good category. Based on these results, it can be concluded that web-based teaching materials are feasible to be applied to in the subject of school curriculum development.